Grazing time and milk production of crossbred cows in a rotational area of Elephant grass and Tanzania grass - Lima, Maria Lúcia Pereira; Berchielli, Telma Teresinha [UNESP]; Leme, P. R.; Nogueira, José Ramos; Pinheiro, Maria da Graça (My University, 2004)
This study was carried out in January of two consecutive years. The objective was to evaluate the grazing time, the grazing rate and the milk production of crossbred cows, managed in two rotational grazing areas, one with elephant grass (Pennisetum purpureum Schum. cv. Guaçu) and another one with Tanzania grass (Panicum maximum Jacq. cv. Tanzania), both with natural shade in the rest area. The experiment was divided in two phases, the first with 12 cows that remained day and night in the paddock and were milked twice a day. In the second phase 15 cows were observed and remained 10.43 hours in the paddock during the day, and were kept in a corral during the night. Each cow was observed every 15 minutes. Grass specie had no effect on milk production in the two phases of the experiment. The grazing time was 564 and 474 minutes and the grazing rate was 28.7 and 24.4 minutes/hour for the Elephant grass and Tanzania grass, respectively, in first phase. In the second phase,the grazing time was 461 and 426 minutes and the grazing rate was 42.7 and 39.4 minutes/hour for the Elephant grass and Tanzania grass, respectively. Correlations were observed (P<0.01) between grazing rate and the minimum temperature (-0.68), the maximum temperature (-0.76), the relative humidity (0.44) and the THI (-0.76).
Keywords: Behavior; Bovine; Environment; Panicum maximum; Pennisetum purpureum; Bovinae; elephant; Panicum; Pennisetum; Pennisetum glaucum